Identification of key residues involved in the neuraminidase antigenic variation of H9N2 influenza virus - Wang, Fei (Emerg Microbes Infect, 2021)
Influenza A H9N2 virus causes economic loss to the poultry industry and has likely contributed to the genesis of H5N1 and H7N9 viruses. The neuraminidase (NA) of H9N2 virus, like haemagglutinin, is under antibody selective pressure and may undergo antigenic change; however, its antigenic structure remains to be elucidated. In this study, we used monoclonal antibodies (mAbs) to probe the H9N2 viral NA residues that are key for antibody binding/inhibition. These mAbs fell into three groups based on their binding/inhibition of the NA of H9N2 viruses isolated during 1999–2019: group I only bounded the NA of the early 2000 H9N2 viruses but possessed no neutralizing ability, group II bounded and inhibited the NA of H9N2 viruses isolated before 2012, and group III reacted with most or all tested H9N2 viruses. We showed that NA residue 356 is key for the recognition by group I mAbs, residues 344, 368, 369, and 400 are key for the binding/inhibition of NA by group II antibodies, whereas residues 248, 253, and the 125/296 combination are key for neutralizing antibodies in group III. Our findings highlighted NA antigenic change of the circulating H9N2 viruses, and provided data for a more complete picture of the antigenic structure of H9N2 viral NA.